Application of Dijkstra Algorithm in Determining Transportation Costs for Tourist Attractions in Lombok Island Based on the Shortest Path - M. Afdhaluzzikri; Lalu Djatmika Santriawan; Ermawati Sapni; M. Setyo Nugroho; Mamika Ujianita Romdhini (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: Lombok Island is known as an attractive tourist destination with natural beauty and unique culture. The growth of the tourism sector is very important for regional economic development. Lombok Island often faces challenges in its transportation system, including complex routes, varying road conditions, and traffic problems. Method: In this research, the data used were 30 tourist attractions on the island of Lombok sourced from the Tourism Office. Tourist attractions in Lombok are represented by vertices in the graph. Then the edges represent roads connecting tourist attractions and the weights represent the cost of getting to each tourist attraction from a starting vertex. Then, to determine the minimum transportation cost for each tourist attraction based on this graph, we use Dijkstra algorithm based on the shortest path for each tourist attraction. Result: The minimum transportation costs for each tourist attraction are obtained based on the shortest route for each tourist attraction on Lombok Island. Contribution: The application of Dijkstra algorithm can be a solution to overcome some of these challenges by determining the shortest path and optimizing transportation costs.